Metastases of papillary radioiodine-refractory thyroid cancer in the parapharyngeal lymph node: clinical case - N. A. Ognerubov; T. S. Antipova (Опухоли головы и шеи)
Introduction. Papillary thyroid cancer (PTC) usually metastasizes into the central and lateral lymph nodes (LNs) of the neck. Metastases into the retropharyngeal and parapharyngeal LNs are rare. Their presence attests to aggressive PTC.The study objective is to describe a rare case of metastases of papillary radioiodine-refractory PTC into the parapharyngeal LN.Clinical case. In 2015, female patient K., 40 years old, underwent thyroidectomy due to PTC. Histological examination verified papillary PTC with growth through the capsule and ingrowth into the surrounding tissues and muscles. In a separately admitted LN, metastases of the same cancer were observed. One year later, regional metastases in the lateral neck LNs were detected. Radioiodine therapy (activity 131I 4.5 GBq) was performed followed by fascial circular section of the neck tissues on the right per thyroid type. Morphological examination verified presence of papillary PTC metastases in 4 LNs. In January of 2018, positron emission tomography showed metastases in the paratracheal LNs. Central neck lymph node dissection was performed. Per histological conclusion, fat tissue and LN contained multiple metastases of papillary PTC. In October of the same year, repeat radioiodine therapy (activity 131I 3.0 GBq) was performed. Thyroglobulin levels increased. In June of 2020, repeat positron emission tomography showed a single metastasis in the parapharyngeal LN. Due to small size of the metastasis and absence of signs of progression, dynamic follow-up and hormone therapy were suggested to the patient.Conclusion. Metastatic involvement of parapharyngeal LNs is rare, especially in radioiodine-refractory PTC. They can be detected both during primary diagnosis and after the treatment during dynamic follow-up, as well as a single manifestation of PTC, which should be taken into account during differential diagnosis.